2019
DOI: 10.3996/082018-jfwm-072
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns of Bats During the Fall and Spring Along Ridgelines in the Central Appalachians

Abstract: Many central Appalachian ridges offer high wind potential, making them attractive to future wind-energy development. Understanding seasonal and hourly activity patterns of migratory bat species may help to reduce fatalities at wind-energy facilities and provide guidance for the development of best management practices for bats. To examine hourly migratory bat activity patterns in the fall and spring in Virginia in an exploratory fashion with a suite of general temporal, environmental, and weather variables, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…In birds, it has repeatedly been shown that the relative influence of different weather variables on migration phenology is strongly species‐dependent but also context‐dependent (Gordo, 2007; Haest et al., 2018b, 2019; Shaw, 2016), and a similarly diverse response to weather has been suggested for bats (Muthersbaugh et al., 2019). Therefore, future studies on other bat species and populations may find our results of wind being highly important for spring migration and precipitation for autumn migration timing to be specific for Brazilian free‐tailed bats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In birds, it has repeatedly been shown that the relative influence of different weather variables on migration phenology is strongly species‐dependent but also context‐dependent (Gordo, 2007; Haest et al., 2018b, 2019; Shaw, 2016), and a similarly diverse response to weather has been suggested for bats (Muthersbaugh et al., 2019). Therefore, future studies on other bat species and populations may find our results of wind being highly important for spring migration and precipitation for autumn migration timing to be specific for Brazilian free‐tailed bats.…”
Section: Discussionmentioning
confidence: 98%
“…This may explain why migration in Brazilian free‐tailed bats is not driven by temperature but by precipitation and wind—contrary to species in regions with more extreme inter‐seasonal temperature differences, for example, at higher latitudes. Some studies of migratory bats (at higher latitudes) in northern Europe or North America have indeed suggested that temperature plays an important role in migration timing (Jonasson & Guglielmo, 2019; Muthersbaugh et al., 2019; Pettit & O'Keefe, 2017; Roby et al., 2019; Rydell et al., 2014; Smith & McWilliams, 2016), although temperature was often investigated alone, neglecting possible precipitation and wind effects. However, it is possible that wind and precipitation become primary drivers of migratory timing in regions where a minimum temperature threshold for survivability is met throughout the migration period.…”
Section: Discussionmentioning
confidence: 99%
“…As SDMs can be interpreted as conductance maps, we used an average of both spring and fall months (March, April, May and August, September, October, respectively) to assess potential corridors between winter and summer occurrences. These time periods are based on previously published distributions of occurrences (Cryan, 2003), previous SDM modeling (Hayes, Cryan & Wunder, 2015), wind farm fatality data (Arnett et al, 2008), radio telemetry (Walters et al, 2006), and acoustic data (Muthersbaugh et al, 2019). Using Circuitscape (Shah & McRae, 2008), we set our start ("source") and end ("ground") points based on the hypothesized direction of migration.…”
Section: Migratory Pathwaysmentioning
confidence: 99%
“…These data provide further evidence that operational mitigation strategies at wind energy facilities could help protect migratory bat species and could be used to inform siting decisions for proposed wind energy facilities to lessen the potential impacts on migratory bats that use Appalachian ridges as their primary migration corridors. Publication Muthersbaugh, M.S., Ford, W.M., Powers, K.E., and Silvis, A., 2019, Activity patterns of bats during the fall and spring along ridgelines in the central Appalachians: Journal of Fish and Wildlife Management,v. 10,no.…”
Section: Pre-and Post-hibernation and Migratory Activity Of Bats In Tmentioning
confidence: 99%